PENGARUH PRELOADING TERHADAP LAMA WAKTU KONSOLIDASI PADA TAHAP PRECONSTRUCTION STUDI KASUS PESISIR KOTA SEMARANG: PENGARUH PRELOADING TERHADAP LAMA WAKTU KONSOLIDASI PADA TAHAP PRECONSTRUCTION STUDI KASUS PESISIR KOTA SEMARANG - Widoanindyawati, Vemi; Lestari, Nor Puji; Triwardaya; Kusumastuti, Dianita Ratna; Marsudi; Amal, Andi Syaiful; Sulistiawati, Baiq Heny (Bangun Rekaprima, 2025)
The problem of soft clay soil is currently one of the most worrying soil problems due to the increasing use of soft soil areas for construction needs. The main problem with soft clay soil is its nature which easily absorbs water but is difficult to release the water. The large amount of soft soil in the coastal area of Semarang City implies that in the construction process in the area, it is necessary to consider consolidation reduction. Soft clay soil takes a long time to reach 90% consolidation. This is because the permeability of soft clay soil is very small so that the process of dissipating water out is quite long. This dissipation process can be accelerated using engineering techniques, one of which is preloading. This process will further accelerate the consolidation process. This study was conducted to obtain the optimization of the embankment area against land subsidence on the coast of Semarang City using the numerical analysis method. From the research results, various variations were obtained for the area of embankment for a soil depth of 20 meters with a size of 30 x 30, the decline that occurred was 1.37 cm, a size of 40 x 40, the decline that occurred was 1.552 cm, a size of 50 x 50, the decline that occurred was 1.772 cm. While for the sea decline according to Steinbener